Implementation and performance evaluation of AODV-PSO with AODV-ACO - ., Kavita; Sahai, Prashant; Mittal, Sonu (International Journal of Engineering and Technology, 2018)
AODV gives a course to correspondence while the bunch head is chosen utilizing PSO, in light of the separation from the group part hub to sink hub and the lingering vitality in that hub. Reproduction comes about demonstrate that the inspiration of this work enhances the lifetime of the system remarkably. The Performance of Wireless Sensor Network is upgraded by the proposed Algorithm in light of AODV with PSO convention as far as expanded Packet conveyance proportion, diminishing the normal deferral, expanded normal throughput and diminishing aggregate vitality utilization amid execution.